Dynamic risk assessment and management of domino effects and cascading events in the process industry - Cozzani, Valerio; Reniers, Genserik L. L. (Amsterdam, Netherlands : Elsevier, 2021)
Dynamic Risk Assessment and Management of Domino Effects and Cascading Events in the Process Industry provides insights into emerging and state-of-the-art methods for the dynamic assessment of risk and safety barrier performance in the framework of domino effect risk management. The book presents methods and tools to manage the risk of cascading events involving the chemical and process industry. It is an ideal reference for both safety and security managers, industrial risk stakeholders, scientists and practitioners. In addition, laymen may find the state-of-the-art methods concerning domino effects (large-scale accidents) and how to prevent their propagation an interesting topic of study.
Includes bibliographical references and index.
Keywords: Industrial safety -- Management; Risk assessment; Chemical industry -- Safety measures